Epistemological Transformation of ʿUrf in the DSN-MUI Fatwa on E-Commerce: A Maqāṣid al-Sharīʿah Based Analysis - Sanuri; Mubarok, Nafi'; Musafa’ah, Suqiyah; Irama, Yoga (Al-Manahij: Jurnal Kajian Hukum Islam, 2025)
The rapid growth of digital platforms in global commerce has reshaped conventional transactional norms, including among Indonesian Muslims, raising normative debates on the legitimacy of e-commerce within Islamic jurisprudence. While prior studies have addressed e-commerce in Islamic legal discourse, few have examined the transformation of ʿurf (customary practice) as a legitimate legal source in the digital age. This study introduces the DigitalʿUrf Alignment Model (DUAM), an integrative legal-epistemological framework that systematizes the adaptation of classical ʿurf to digital contexts through maqāṣid al-sharīʿah based validation. Employing a qualitative-normative approach, the research analyzes Fatwa No. 146/2021, issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), classical and contemporary fiqh sources, and emerging digital transaction models. It integrates concepts from uṣūl al-fiqh, maqāṣid al-sharī‘ah, and socio-philosophical reasoning to reconceptualize ʿurf as a dynamic category of legal interpretation. The findings affirm that digital ʿurf, structured through DUAM, enables its institutionalization as a normative legal source for fatwa and provides a scalable method for integrating classical jurisprudence with digital finance regulations.